2013
DOI: 10.1016/j.freeradbiomed.2013.08.162
|View full text |Cite
|
Sign up to set email alerts
|

Thiocyanate potentiates antimicrobial photodynamic therapy: In situ generation of the sulfur trioxide radical anion by singlet oxygen

Abstract: Antimicrobial photodynamic therapy (PDT) is used for the eradication of pathogenic microbial cells and involves the light excitation of dyes in the presence of O2, yielding reactive oxygen species including the hydroxyl radical (•OH) and singlet oxygen (1O2). In order to chemically enhance PDT by the formation of longer-lived radical species, we asked whether thiocyanate (SCN−) could potentiate the methylene blue (MB) and light-mediated killing of the gram-positive Staphylococcus aureus and the gram-negative E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 48 publications
5
37
1
Order By: Relevance
“…34 A similar addition mechanism was proposed in our previous paper 35 in which we suggested a similar mechanism for the oxidation of thiocyanate by singlet oxygen.…”
Section: Resultssupporting
confidence: 75%
“…34 A similar addition mechanism was proposed in our previous paper 35 in which we suggested a similar mechanism for the oxidation of thiocyanate by singlet oxygen.…”
Section: Resultssupporting
confidence: 75%
“…As described by other researchers, 19,23,[29][30][31] ROS may be one of the key factors in SDT-induced cell damage. Excessive ROS may damage lipids, proteins, and DNA, and cause mitochondrial dysfunction, deregulation of ion balance, and loss of membrane integrity.…”
Section: Discussionmentioning
confidence: 63%
“…Our laboratory has recently reported that thiocyanate anion can also potentiate antimicrobial PDI mediated by MB 36 and has gained some preliminary evidence that other simple inorganic salts (such as iodide anion) are also able to potentiate antimicrobial PDI, and these results will be reported in due course.…”
Section: Discussionmentioning
confidence: 88%